Towards Security Metrics Combining Risks of Known and Zero-day Attacks: Work in Progress - Marbukh, Vladimir (IEEE/IFIP Network Operations and Management Symposium, 2023)
This paper reports on work in progress on security metrics combining risks of known and zero-day attacks. We assume that system security is modelled by Attack Graph (AG), where attack paths may include a combination of known and zeroday exploits and impact of successful attacks is quantified by system loss function. While set of feasible zero-day exploits and composition of each attack path are known, only estimates of likelihoods of known exploits are available. After averaging the system loss function over likelihoods of known exploits, we propose addressing uncertain likelihoods of zero-day exploits within framework of robust risk metrics. Assuming some prior likelihoods of zero-day exploits, robust risk metrics are identified with the worst-case Bayesian AG scenario subject to a controlled deviation of actual likelihoods of zero-day exploits from their priors. The corresponding worst-case scenario is defined with respect to the system losses due to a zero-day attack. We argue that the proposed risk metric quantifies potential benefits of system configuration diversification, such as Moving Target Defense, for mitigation of the system/attacker information asymmetry.